A few reflections on the subject of literature, English Language and the teaching/ learning process. - Brandão, Izabel (1999)
The teaching of foreign languages has always worked apart from literature. The approach to the literary text, if (and when) made, is usually based on the use of simplified texts or stylistics. In the former case, the literary text simply stops being an authentic text to work merely as a tool for the learning of vocabulary (Brumfit and Carter: 1987). As far as stylistics is concerned, the situation is a little more complex. However valid the approach may be for linguistic purposes, if misused, it can become an enormous obstacle in the process of learning literature, especially in what refers to the students’ motivation.